A laboratory scale IoT-based measuring of the solar photovoltaic parameters - Arsyad Cahya Subrata; Tole Sutikno; Sunardi Sunardi; Anggit Pamungkas; Watra Arsadiando; Ahmad Raditya Cahya Baswara (International Journal of Reconfigurable and Embedded Systems (IJRES), 2022)
Harvesting solar energy as a renewable energy source has received significant attention through serious studies that could be applied massively. However, the nonlinear nature of photovoltaic (PV) concerning the surrounding environment, especially irradiation and temperature, affects the resulting output. Therefore, the correlation between environmental parameters and PV's energy needs to be studied. This paper presents a design for measuring solar PV parameters monitored on a laboratory scale. The monitoring is based on internet of things (IoT) technology analyzed in realtime. The system was tested in various weather conditions for 18 hours. The results obtained indicate that the output voltage was influenced by the lighting factor of the PV and the surrounding temperature.